Transportation challenges in the movement and distribution of agricultural products in Ibadan region (2011)
The study examined the movement and. distribution of agricultural produce in Ibadan region. 228 transport operators were purposively sampled and served with structured questionnaire. Focus Group Discussion and In-depth Interview were also used to elicit information from different seller associations. Findings indicated that more than 95% of transport operators do not have more than secondary education while only 5.2% of them earn more than N10, 000 monthly. Also, 86% of them work more than 12 hours per day. On the average, market sellers lose about N2, 500 and N6,000 monthly during dry and rainy seasons respectively from agricultural produce waste due to crop rots. Deteriorating road condition, extortion by law enforcement agencies, fuel scarcity (diesel engine trucks) and the influence of road transport union were identified as problem's militating against free flow of agricultural produce in the study area. The paper suggested the urgent need for efficient road maintenance through participatory approach, adequate enforcement of traffic laws as well as the need for government to develop appropriate rural transport policy to address the perennial problems of rural transportation in the country.